Stephen Leacock, a reappraisal - Staines, David, 1946- (Re-appraisals, Canadian writers, 1986)
This collection of essays explores the many dimensions of the writings of Stephen Leacock, the well-loved Canadian author of Sunshine Sketches of a Little Town.